Domestic Credit and Inflation Rate Shock: A New Empiric Evidence from Nigeria - Adegboyega, Soliu Bidemi; Odusanya, Ibrahim Abidemi; Ogede, Jimoh Sina; Atoyebi, Olayinka Esther (EkBis: Jurnal Ekonomi dan Bisnis, 2023)
The study evaluates the relationship between domestic credit and Nigeria's inflation rate analysing data spanning from 1986 through 2020. The research is ex-post in nature, hence the study employed statistical analysis models to build a predictive assessment for inflation, leveraging on the Autoregressive distributed lag model (ARDL) and the Granger Causality test to ascertain the magnitude of the association and the direction of causation, separately. The study confirms the complexities of Nigeria's relationship between domestic credit and inflation, with economic growth maintaining a positive and insignificant relationship with inflation (INF), while credit to the private sector (CPS) and interest rates have a negative and insignificant relationship with inflation in the long run. Furthermore, in the short run the coefficient of error correction model showed a negative sign, suggesting a short run effect between inflation rate and domestic credit.  The findings reaffirm the one-way relationship between inflation and private sector domestic credit. It is advised that funding tools be used efficiently and effectively to fulfil desired investment, competitiveness, and economic growth drives.